Efforts to Regenerate Local Tourism: Using Empty Land as a Fishing Spot - Giovani, Nurya; Diah Pratami, Riska; Anggi N U, Elfina; Arifin, Rizal (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
Kesugihan Village is an area located in the highlands, approximately 5.6 km from the sub-district government center. Kesugihan Village has a spring that is located not far from residential areas. However, due to the lack of public concern for the environment of the spring, it is not used as a tourist attraction. Kesugihan Village has a tourist destination, Sekar Wilis Park, which is not far from residential areas and water sources, so the village and community should utilize existing facilities and natural resources. However, the park is no longer operational due to a lack of maintenance by the community, youth organizations, and the village government. The 01 KKN UMPO 2023 team in Kesugihan Village wants to revive empty land by changing the swimming pool into a fishing pond so that this effort can increase the motivation of residents and the village government to improve the residents' economy.